The Free Trade Area of the Americas: positive outcomes for Brazil and the global community - Jasmer, Michael David (2007)
This document discusses Brazil and the Free Trade Area of the Americas (FTAA). Since the FTAA is only a proposed agreement and trade apparatus at the moment, NAFTA is used as a working model and its influence on and benefit for Mexico and that country’s economy.